Sanchita (YSWB 2014/2) and Anushka (YSWB 2011-10-1) - two yellow sarson (Brassica rapa var. yellow sarson L.) varieties notified for West Bengal: SANCHITA AND ANUSHKA - TWO YELLOW SARSON VARIETIES NOTIFIED FOR WEST BENGAL - AMITAVA DUTTA; K N MANDAL; S K SAHOO; R DAS; S ROY; S SARKAR; SHANKAR BHUJBAL; ARCHANA RAI; SANJAY J JAMBHULKAR (Journal of Oilseeds Research, 2021)
Sanchita (YSWB 2014/2)was developed through crossing betweenRajendra Sarson and PYS 2005 and Anushka (YSWB 2011-10-1) was developed through crossing between Benoy (B-9) and Rajendra Sarson. Both the varieties were tested during rabi 2010-11 to 2015-16 at different locations with National Checks (NC) YSH-0401, NRCYS-05-02 and PT-303, the latest release (LR) Pitambari and the Zonal Check (ZC) B-9 and Panchali. Sanchita has the distinction of attaining 24.04% yield advantage over YSH-0401, 6.7% over Pitambari and 26.7% over B-9. It also registered 8% higher oil yield advantage over YSH-0401, 7% over Pitambari and 32.9% over B-9. Anushka registered 29% higher mean seed yield during 2010-11 and 18% higher mean seed yield during 2012-13 over B-9. During 2014-15, Anushka also recorded 8.7%, 9.0% higher seed yield and 13.9 and 14.2% higher oil yield over the two toria varieties Panchali and PT-303, respectively. It was 10-12 days earlier in maturity than Benoy. Superior performance of Sanchita and Anushka in the coordinated and multilocation trials over the years, led to their notification by Central Variety Release Committee (CVRC) for release in West Bengal. Molecular marker analysis depicted distinct SSR alleles for Sanchita and Anushka compared to Benoy.